PENGARUH GREEN PERCEIVED RISK DAN GREEN PERCEIVED VALUE TERHADAP GREEN REPURCHASE INTENTION DENGAN GREEN TRUST SEBAGAI MEDIASI - Owen, Oliver; Pranatasari, Fransisca Desiana; Kurniawati, Lucia (Parsimonia - Jurnal Ekonomi dan Bisnis, 2024)
The phenomenon of global warming is a crucial problem today, efforts that can be made are to create a green movement or go green to overcome environmental damage and at the same time realize a sustainable environment. One of the efforts of the Indonesian Government to respond to this phenomenon is by launching a Green Economy to create Sustainable Development. MSMEs are one of the joints of the economy that can boost the realization of the Green Economy. Therefore, Indonesian MSMEs must be able to create a quality green brand and product. The creation of products and brands must pay attention to marketing science, especially green marketing for green products. Marketing green products must consider bad consumer perceptions, good consumer perceptions, and consumer trust to assess how likely consumers are to make repeat purchases. This study aims to determine the effect of green perceived risk and green perceived value on green repurchase intention with green trust as a mediation study on visitors to the Wiguna Yogyakarta market. The population in this study were all visitors to the Wiguna Yogyakarta market. This study uses a non-probability sampling technique with a purposive sampling method. This study used 130 respondents as samples whose data were obtained through the distribution of online questionnaires in the form of Google Forms. The analysis technique in this study is Partial Least Square with the SmartPLS 4 application. The results of this study indicate that Green Perceived Risk has a significant negative effect on Green Repurchase Intention, Green Perceived Value has a significant positive effect on Green Repurchase Intention, Green Perceived Risk has no effect on Green Repurchase Intention with Green Trust as a mediator, Green Perceived Value has an effect on Green Repurchase Intention with Green Trust as a mediator.